Profil Mikroskopis Jaringan Ginjal Mencit (Mus Musculus) yang Difiksasi dengan Madu Konsentrasi 10% Selama 24 Jam - Tasya Vita Brilian (Poltekkes Kemenkes Semarang, 2021)
Fixation is used to maintain tissue structure in its original form â€œlife-like stateâ€ and can protect proteins and tissue components from degeneration. The solution commonly used is 10% NBF. Formaldehyde is chemical substance that is toxic and not environmentally friendly, several studies have shown alternative substitutes fixation, one of which is the honey solution. The study of Mohammed et al (2020) fixated tissue with honey 10% and 20% shown good coloring properties and similar clarity to fixated with formalin 10%. Honey has acidic and dehydrating properties allow most microorganisms to be killed so that tissues will last for a long time. The research objective is to findout the description of microscopic of mice (Mus musculus) kidney tissue which were fixation using 10% honey solution for 24 hours. The research is included in qualitative descriptive research. The research design used was a non-eksperimental with a purposive sampling study approach. The sample used was 32 preparation with total of microscopic overview is 160. Microscopic image of mice (Mus musculus) kidney tissue fixed using 10% honey solution for 24 hours in 80 visual fields were 12.5% of the preparations is not good and 87.5% is good preparations. The microscopic image of mice (Mus musculus) kidney tissue fixed using 10% NBF is better than of the microscopic image of mice (Mus musculus) kidney tissue fixed with 10% honey for 24 hours.